Mental Health Literacy Among General Practitioners in Israel: A Qualitative Study. Issue 1 (January 2023) - Khatib, Anwar; Ben-David, Vered; Abo-Rass, Fareeda; Gelkopf, Marc; David, Roe
In recent years, general practitioners (GPs) have become more involved in treating people with mental disorders. This study examined the mental health literacy of GPs in Israel, based on Jorm's conceptual framework. Twenty-one GPs participated in a semi-structured, in-depth interview. The data were analyzed thematically, guided by Jorm's six mental health literacy dimensions. The GPs generally reported that they could identify symptoms of mental disorders, mainly noted genetics as the cause and risk factor for mental disorders, did not believe that self-care methods could alleviate mental disorders, and regarded social workers—as distinct from psychologists—as particularly helpful in their work with people with mental disorders. The findings, which have implications for families, emphasize the importance of providing GPs with ongoing educational opportunities to ensure they remain knowledgeable and skilled in mental health.